CHALLENGES IN RESOURCE ALLOCATION (5M) TOWARDS COST CONTROLLING IN ENGINEERING PROCUREMENT CONSTRUCTION (EPC) FABRICATION OIL AND GAS MEGAPROJECTS - Farrah Rina Mohd Roshdi; Kharizam Ismail; Nor Suzila Lop; Lilawati Ab Wahab (International Journal of Accounting, Finance and Business, 2022)
The resources contain a money cycle involving machinery, manpower, and materialsaligned with a suitable method (5M) in a fabrication project. However, given the currenteconomic climate, it is critical to keep costs under control and realign its mission. As a result,this study objectives and aims to use ATLAS-ti to analyze preliminary survey data on resourceallocation management challenges in oil and gas EPC fabrication projects. The survey datawas gathered through qualitative research involving interview techniques with ten (10) expertsin Engineering, Procurement, and Construction (EPC). The results reveal that the factorsaffecting resource allocation (5M) are a lack of support from top management, poor resourceutilization, and management in the EPC project.The atlas-ti network analysis revealed thatmoney had a more significant impact on the allocated resources. The budget issue, in which thebudget allocation does not meet the project requirements, is a significant source of procurementchallenges. The challenges of resource allocation management, which control cost overrun in5M of Oil and Gas Fabrication, are expected to be revealed in this study.